2021
DOI: 10.1038/s41467-021-25960-2
|View full text |Cite
|
Sign up to set email alerts
|

Confronting false discoveries in single-cell differential expression

Abstract: Differential expression analysis in single-cell transcriptomics enables the dissection of cell-type-specific responses to perturbations such as disease, trauma, or experimental manipulations. While many statistical methods are available to identify differentially expressed genes, the principles that distinguish these methods and their performance remain unclear. Here, we show that the relative performance of these methods is contingent on their ability to account for variation between biological replicates. Me… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
418
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 498 publications
(524 citation statements)
references
References 115 publications
14
418
1
Order By: Relevance
“…Furthermore, our own investigation of false positive rate in scRNAseq, when cells were randomly assigned to two groups, also yielded no false DEGs, consistent with findings in Soneson and Robinson (2018), who performed similar analyses over multiple scRNAseq datasets and found low (sometimes no) false discoveries when using the same statistical analysis approach that we used (Wilcoxon). In contrast to these findings, Squair et al (2021) recently published findings suggesting that divergence of scRNAseq differential expression analysis from that of matched bulk RNAseq represented false positives in scRNAseq. This conclusion was mostly based on simulations where they randomly assigned pseudo-replicates or real replicates to treatment groups.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations
“…Furthermore, our own investigation of false positive rate in scRNAseq, when cells were randomly assigned to two groups, also yielded no false DEGs, consistent with findings in Soneson and Robinson (2018), who performed similar analyses over multiple scRNAseq datasets and found low (sometimes no) false discoveries when using the same statistical analysis approach that we used (Wilcoxon). In contrast to these findings, Squair et al (2021) recently published findings suggesting that divergence of scRNAseq differential expression analysis from that of matched bulk RNAseq represented false positives in scRNAseq. This conclusion was mostly based on simulations where they randomly assigned pseudo-replicates or real replicates to treatment groups.…”
Section: Discussionmentioning
confidence: 87%
“…Particularly when replicateto-replicate variation was high, large numbers of false positives were found in this analysis. Squair et al (2021) also used an RNAscope assay to attempt to confirm scRNAseq-derived DEGs in a model of spinal cord injury and found low replicability there. RNAscope is commonly used to confirm scRNAseq findings so it is unclear why replicability is typically reported in other studies but not found in Squair et al (2021).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another likely cause for the observed variability is that we were limited to performing the differential expression analyses on a cell-by-cell basis, an approach which lacks power and gives rise to a higher frequency of false positives. If we had had more biological replicates, we could have performed a pseudo-bulk analysis which might have shed further light on the common responses of SGCs to different nerve injuries (Crowell et al, 2020;Squair et al, 2021).…”
Section: Discussionmentioning
confidence: 99%